Comparative Genomics Analysis Demonstrated a Link Between Staphylococci Isolated From Different Sources: A Possible Public Health Risk - Cave, Rory; Misra, Raju; Chen, Jiazhen; Wang, Shiyong; Mkrtchyan, Hermine V. (Frontiers in Microbiology, 2021)
Coagulase-negative staphylococci (CoNS) have been recovered from different ecological niches, however, little is known about the genetic relatedness of these isolates. In this study, we used whole genome sequencing to compare mecA positive (mecA+) Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis isolates recovered from hand-touched surfaces from general public settings in East and West London with data of isolates deposited to European Nucleotide Archive (ENA) by other research groups. These included isolates associated with hospital settings (including those recovered from patients), healthy humans, livestock, pets, plants and natural and other public environments. Using core and accessory phylogenetic analyses we were able to identify that the mecA+ S. epidermidis and S. haemolyticus isolates recovered from general public settings were genetically related to isolates recovered from the bloodstream, urinary tract and eye infections. S. epidermidis isolates recovered in our study were also shown to be genetically related to isolates previously recovered from livestock/livestock housing, whereas S. haemolyticus isolates were genetically related to isolates recovered from a dog and kefir (fermented cow milk drink). MecA+ S. hominis isolates were not genetically related to any isolates recovered from clinical samples but were genetically related to isolates recovered from mosquitoes, air samples (residential areas) and kefir. All three species showed to have genetic relatedness to isolates recovered from healthy humans. These results show that CoNS isolates in this study share genetic similarities with those of different lineages and that mecA+ S. epidermidis and S. haemolyticus isolates found in general public settings in this study may pose a risk to public health.